2νββ-decay to first 2+ states with partial isospin symmetry restoration from spherical QRPA calculations *Supported by National Natural Science Foundation of China (11505078, 1164730), "Light of West China" Program and key research program (XDPB09-2) from Chinese Academy of Sciences. (August 2020) - Fang 房, Dong-Liang 栋梁; Faessler, Amand
Abstract: Using partially restored isospin symmetry, we calculate the nuclear matrix elements for a special decay mode of a two-neutrino double beta decay – the decay to the first 2 + excited states. Employing the realistic CD–Bonn nuclear force, we analyze the dependence of the nuclear matrix elements on the isovector and isoscalar parts of proton–neutron particle–particle interactions. The dependence on the different nuclear matrix elements is observed, and the results are explained. We also provide the phase space factors using numerical electron wavefunctions and properly chosen excitation energies. Finally, we present our results for the half-lives of this decay mode for different nuclei.